Open Building Research - Amar, Georges; Borasi, Giovanna; Brescia, Paolo; Brescia, Paolo; Desvigne, Michel; Horn, Roni; Principi, Tommaso; Principi, Tommaso (Birkhäuser, 2023)
Architectural work in dialogue with different disciplines Founded by Paolo Brescia and Tommaso Principi as a design network between Milan, London and Mumbai, OBR explores new modes of contemporary living, developing an architecture that responds sensitively to and stimulates interaction with its environment, while adapting to the changing needs of society. OBR's work strives to promote a sense of community enhancing individual identities. In this book, the architects present their work as a communal endeavor. They engage influential people in transdisciplinary dialogues that extend beyond architecture itself, questioning its autonomy and offering new perspectives on its potential and relevance. The monograph showcases a selection of twenty-four international projects by OBR that address key social issues through the medium of architecture. The first monograph on OBR's work Selection of 24 international projects presented in texts, plans and photographs Transdisciplinary dialogues with Roni Horn, Michel Desvigne, Giovanna Borasi, and Georges Amar